Pengenalan Dasar Komputer dan Pemanfaatannya dalam Mendukung Literasi Teknologi Informasi Siswa - Sitohang, Norenta; Sianturi, Ronda Deli (CV. Devi Tara Innovations, 2026)
The development of information technology in the digital era requires students to possess technological literacy skills as a foundation for facing modern educational challenges. However, many elementary school students still lack basic understanding of computers and their utilization in learning activities. This community service program aimed to introduce basic computer concepts and train students in utilizing technology to support information technology literacy. The methods used included lectures, demonstrations, and hands-on practice conducted at SD Negeri 106167 Lantasan Baru. The materials covered hardware and software introduction, word processing applications, and responsible internet usage. The results showed an improvement in students’ understanding of computer components, their ability to use basic applications, and awareness of the importance of digital literacy. This program contributes positively to enhancing students’ readiness for digital-based learning and supporting the development of 21st-century skills.